Blast Resistance of Rice Induced by Ag-antibiotic 702 - Neng, Hu; Shuai, Yang; Zhihuo, Lei; Xiaorong, Tu; Guoquan, Tu; Lin, Huang (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
To explore rice blast resistance induced by Ag-antibiotic 702, different concentrations of Ag-antibiotic 702 were spayed on susceptible variety Luliangyou 996 at three-leaf and one-heart stage, to screen the optimal concentration for inducing rice blast resistance. Ag-antibiotic 702 was sprayed at seven different growth stages of rice, to determine the best growth stage for induced blast resistance and duration of blast resistance. Various treatments were inoculated with spore fluid of Magnaporthe grisea at 4 d post spraying, and disease index and incidence rate as well as induction effect of different treatments were investigated after 7 d. The results showed that six concentrations of Ag-antibiotic 702 could induce rice resistance against blast, and 15 μg/mL led to the highest blast resistance; spraying 15 μg/mL Ag-antibiotic 702 at seven different growth stages could induce rice resistance against blast ; the three-leaf and one-heart stage was the best growth stage for inducing rice blast resistance, and the relative induction effect reached 56.56% ; rice blast resistance was the highest at 48 -96 h post spraying, and duration of induced rice blast resistance exceeded 144 h. The study will provide useful experimental data for further development of Ag-antibiotic 702 and application of pre- vention and control methods against rice blast.